Konsep Mixed Use pada Kawasan Rumah Susun Kecamatan Mariso Kota Makassar - Nur Adyla S; Louis Santoso; Wiwik Wahidah Osman (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2013)
Development of a region or city in Indonesia have led to the construction of housing and urban settlements in the sub region, the problems that often happens is thatthe populationisgrowing, with the increase of population the demand forhousing increases, so the solution of these was the construction of housing and settlements in the formof flats. In the city of Makassar, which has a big population have built some flats are located in density residential one point in the Subdistrict Mariso which is a housing project for low-income communities. But the availability of socio-economic infrastructure in the flats of Subdistrict Mariso has not fully meet the needs of residents, giving rise to a far distance, travel time is long and expensive transportation costs incurred residentsof flatstoreachthefacilities and infrastructure. Construction of flats should consider facilities and infrastructure to the need for a means of social and economic activities residents, as it also needs to consider the plan with the concept of mixed land use, which is closer to land rsidential function by means of economic and social infrastructure at a distance that allows the vehicle to achieve non-ization such as walkable, cycling, and facilitated by access to public and transit systems/TOD, to be reduce the mobility of vehicles, and also reduce transportation costs of residents.